CHARACTERISTICS AND TREATMENT OUTCOMES OF PRETERM INFANTS WITH INFECTION AT THE PEDIATRIC CENTER OF BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics and treatment outcomes of neonatal sepsis in preterm infants at the Pediatric Center, Bach Mai Hospital.Subjects and Methods: A descriptive case-series study was conducted on 104 preterm neonates diagnosed with neonatal sepsis in 2024.Results: The proportion of late-onset neonatal sepsis (LONS) was 40.4%, while early-onset neonatal sepsis (EONS) accounted for 59.6%. The proportion of infants whose mothers had infections during pregnancy in the EONS group was 2.7 times higher than that in the LONS group (25.8% vs. 9.5%), with a statistically significant difference (p = 0.039). Tachypnea was observed in 77.9% (81/104) of infants. Chest retractions occurred in 71.2% of cases. Apnea was present in 58.7% of infants, grunting respiration in 47.1%, and decreased oxygen saturation (SpO₂ < 90%) in 48.1% of infants. The median length of hospital stay in the LONS group was 33.5 days, which was longer than that in the EONS group (25.5 days). The use of a single-antibiotic regimen was most common in the EONS group (40.3%), whereas in the LONS group treatment mainly involved the use of more than three antibiotics (54.8%). Ampicillin was the most frequently used antibiotic in both groups. After initiation of empirical antibiotic therapy, the main reason for the first antibiotic modification was based on antibiotic susceptibility testing (36.5%). For subsequent antibiotic changes, the most common reason was antibiotic de-escalation (44.2%).Conclusion: These findings indicate that late-onset neonatal sepsis, which is often acquired in the hospital environment and may be associated with antimicrobial-resistant pathogens, represents a more severe condition requiring more intensive interventions and prolonged treatment, resulting in a longer duration of hospitalization compared with early-onset neonatal sepsis.
Keywords: Neonatal infections, antibiotics, treatment.